Mobile Wireless Middleware, Operating Systems, and Applications - Workshops Mobilware 2009 Workshops, Berlin, Germany, April 2009, Revised Selected Papers - Hesselman, Cristian.; Giannelli, Carlo. (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering,, 2009)
This book constitutes the thoroughly refereed post-workshop proceedings of the Second International Conference on MOBILe Wireless MiddleWARE, Mobilware 2009, held in Berlin, Germany, in April 2009. The 18 revised full papers presented were carefully reviewed and selected; the papers are organized in four different workshops: Ubi-Islands 2009, the first international workshop on interconnecting ubiquitous islands using mobile and next generation networks; WASP 2009, the first international workshop on wireless sensor networks architectures, simulation, and programming; UCPA 2009, the first international workshop on user-centric pervasive adaptation; and BMMP 2009, the first international workshop on business models for new mobile platforms. Two of this were purely technical, one a mixed technical/end user nature, and one focusing on business models.